2012
DOI: 10.1159/000333286
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging in Patients with Transient Ischemic Attack: A Comparison of Computed Tomography and Magnetic Resonance Imaging

Abstract: Background: Brain imaging in stroke aims at the detection of the relevant ischemic tissue pathology. Cranial computed tomography (CT) is frequently used in patients with transient ischemic attack (TIA) but no data is available on how it directly compares to magnetic resonance imaging (MRI). Methods: We compared detection of acute ischemic lesions on CT and MRI in 215 consecutive TIA patients who underwent brain imaging with either CT (n = 161) or MRI (n = 54). An MRI was performed within 24 h in all patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…35,69,81,122,138,150,158,249,251 A recent multicentre study showed that the proportion of patients with final diagnosis of TIA and visible lesion on CT was 23.9%; however, it is unclear if this was just the relevant lesion and in many cases it was an old and irrelevant lesion. 211 In patients with diagnosis of minor stroke, the proportion of patients with a visible relevant lesion on CT ranged from 42% to 52% (ESS data 111 ).…”
Section: Prognosis Among Patients With Suspected Transient Ischaemic mentioning
confidence: 99%
“…35,69,81,122,138,150,158,249,251 A recent multicentre study showed that the proportion of patients with final diagnosis of TIA and visible lesion on CT was 23.9%; however, it is unclear if this was just the relevant lesion and in many cases it was an old and irrelevant lesion. 211 In patients with diagnosis of minor stroke, the proportion of patients with a visible relevant lesion on CT ranged from 42% to 52% (ESS data 111 ).…”
Section: Prognosis Among Patients With Suspected Transient Ischaemic mentioning
confidence: 99%
“…16 More recently, a study of 161 tia patients, who underwent both Ct and Mri, indicated focal Ct abnormalities in seven (4.3%) patients. 26 the overall agreement between Ct and Mri in detecting ischemic lesions was 69%, indicating that approximately one third of identified dWi lesions were missed or misidentified (i.e. chronic lesions classified as acute relevant infarct) on Ct.…”
Section: Imaging Studies In Tia Patientsmentioning
confidence: 99%
“…A transversal diffusion‐weighted series is appreciated in the evaluation of restricted water diffusion in brain tissue as a sign of cytotoxic oedema. DWI has a superior sensitivity in the detection of acute ischaemia compared to CT and shows areas of cytotoxic oedema as soon as 3–11 min after onset of AIS . It is possible to visualize very small ischaemic areas even in the posterior fossa .…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%